T6 Elevated serum Cathepsin K is associated with disease activity in Lymphangioleiomyomatosis and Cathepsin K inhibition is beneficial in vitro and in vivo. (11th November 2022) - Miller, S; Babaei-Jadidi, R; Clements, D; Krymskaya, VP; Johnson, SR
Abstract : Introduction and Objectives: Lymphangioleiomyomatosis (LAM) is a rare multisystem disease of women characterised by lung cysts, lymphatic abnormalities and angiomyolipomas. 'LAM' cells present in the lungs harbour mutations in either TSC1 or TSC2 genes giving rise to constituitive mTOR pathway activation. Lung damage in LAM is thought to result from aberrant protease activation. We previously showed the cysteine protease Cathepsin K (CTSK) was the most strongly expressed protease in LAM compared to control lung, increased with worsening disease and could be activated in LAM lung tissue. Here, we evaluate the inhibition of Cathepsin K in cell and murine models of LAM, and assess levels of CTSK in the sera of patients from a UK cohort of LAM. Methods: TSC2-null cells were treated with the Cathepsin K inhibitor Odanacatib, viability and proliferation assessed. An immunocompetent TSC2-null murine model of LAM was treated with Odanacatib, rapamycin or both, tumour burden and cell proliferation were assessed. Cathepsin K activity was quantified in mouse lung tissue and BAL by Cathepsin K activity assay and ELISA. Serum Cathepsin K was measured in 53 women with LAM with linked phenotype and lung function data. Results: Odanacatib inhibited the proliferation of murine TSC2-null TTJ cells in vitro (IC50 =0.68 nMol, p=0.01). In a murine model of LAM over 6 weeks, Odanacatib reduced Cathepsin K activity in both BAL and lung (p=0.005), decreased the size of lung nodules (p<0.0001), reduced Ki67 immunopositivity in TSC2 null nodules (p=0.01) and tended to be synergistic with rapamycin. Serum Cathepsin K levels in 53 women with LAM were 7.8–84.7 pg/ml (35.3±17.5). Cathepsin K was higher in 27 patients with active LAM (12.4–84.7pg/ml, 40.8±19.0) compared to 26 with stable disease (7.8–62.1, 29.5±13.5), p=0.034 ( figure 1 ). A trend was observed for higher levels of Cathepsin K in patients with lower FEV1 (p=0.067) but Cathepsin K was not associated with serum VEGFD (p=0.13). Conclusions: Our findings suggest that Cathepsin K may be involved in lung damage in LAM and inhibition of Cathepsin K should be investigated further as a treatment for LAM. Please refer to page A208 for declarations of interest related to this abstract.